Understanding resilience in slums using an agent-based model. (March 2020) - Roy, Debraj; Lees, Michael
Abstract: The existence of slums or informal settlements is common to most cities of developing countries. In India, slums contain a wealth of diversity that is masked by a high level of poverty and insufficient access to resources. Recent studies have identified that it is important to assess the resilience of slums as they differ from one slum to another. While many slums are vulnerable to forced evictions, temporary jobs, and constant migration; few slums can respond and recover from external shocks and stress. In this paper, we investigate the resilience of slums based on novel field data from 37 slums in Bangalore. Specifically, we develop an agent-based model to understand how existing social, economic and environmental situation impacts the choices of slums. The paper makes two important findings. First, we find a high social satisfaction has a stabilizing effect, which means that despite more attractive economic opportunities, social satisfaction the slum dwellers derive from living in the neighbourhood of similar contacts is a strong motive to stay. However, given that a lack of economic opportunities causes a decline in the population, the social satisfaction will decrease as a function of the number of social contacts that move. We show that this cascading effect of emigrating population strongly depends on group identity such as religion. Second, we detect different regimes as social satisfaction increase, the population transitions from extinction to positive density dependence to density independence . Therefore, understanding the social capital of a slum community can offer insights into the ability of a slum to recover from external perturbations. Highlights: Understanding the resilience in slums. Interplay of social, economic and environmental factors on the choices of slums. Importance of social capital on the resilience of a slum. Different regimes of slum population based on social satisfaction. Approach to effective policy intervention in slums.